Families that are offered health service by the Family Medicine Outpatient Clinic in Marmara University Medical School [Marmara Üni̇versi̇tesi̇ Tip Fakültesi̇ Ai̇le Heki̇mli̇ǧi̇ Poli̇kli̇ni̇ǧi̇ni̇n saǧlik hi̇zmeti̇ sunduǧu ai̇leler] - (:unkn) unknown (My University, 2009)
Objective: "Family centered health care" is a basic principle of Family Medicine. We aimed to evaluate the health service for families in order t to improve the quality of Family Medicine outpatient-clinic (FMOPC) in Marmara Medical School. Method: In this retrospective, cross-sectional, descriptive study, 245 families (601 patients) who had applied to our outpatient clinic, between January 1999- September 2004, were evaluated according to their characteristics, complaints, consultations and the given therapies. Results: Families form 25% of all policlinic patients. 52.7% were faculty members and their families, and 25% were health professionals from the hospital and their families. Fifty eight percent of the patients were female, 42.3% had visited the FMOPC 3 or more times. The most common complaint was the demand for healthy adult physical examination (14.8%). The most commonly referred clinics were obstetrics and gynecology (11.5%), physical therapy and rehabilitation, dermatology and diet (7.7% for each). The most frequent 5 diagnoses on the first visit were 1-upper respiratory tract infections, 2-hypertension, 3-periodical health examination, 4-dyslipidemia, 5-anemia. Conclusion: Family oriented primary care is demanded from family physicians. But, to deliver that kind of health care there is a need for appropriate infrastructure and manpower. So our clinics in University hospitals must be developed and supported in order to provide good primary family care.
Keywords: Family centered approach; Family medicine; Outpatient clinic; Primary health care